Análisis de datos cinéticos para la producción de ácido láctico por la bacteria Lactobacillus acidophilus en un sustrato complejo (2018)
This research work aims to adjust a kinetic model that satisfactorily describes the production of lactic acid by the bacterium Lactobacillus acidophilus in the fermentation of the selected substrate. First, the fermentation of the complex medium composed of pineapple of the Perolera variety was carried out in an advanced stage of maturation, using the bacterium Lactobacillus acidophilus under controlled conditions of temperature and agitation. During the fermentation, samples were taken every 12 hours for 108 hours to later analyze them in the high performance liquid chromatograph and determine the experimental kinetics of lactic acid production. Subsequently, a bibliographic search was made of analytically resolved kinetic models for the production of lactic acid from other substrates and bacteria, which could possibly be adjusted to the experimental data obtained. Once the models were selected, the non-linear regression of each was performed using the Matlab® software, obtaining as a result the parameters of each model.